GLOBAL DISTRIBUTION AND CROSS-COUNTRY COLLABORATION ON DATA AND ARTIFICIAL INTELLIGENCE ETHICS RESEARCH: A BIBLIOMETRIC ANALYSIS - Wahid, Ratnaria (Jurnal Paradigma Hukum Pembangunan, 2025)
Publications on data and artificial intelligence ethics have grown in importance as more international entities seek to adopt new rules and create international frameworks to manage the same. Concerns remain, however, regarding the fragmented legal landscape and the absence of a unified set of standards for big data and artificial intelligence technology. This study examines data and AI ethical publishing and citation patterns from 1996 to 2022 (26 years). It highlights the leading countries and institutions, prominent research streams, and cross-country collaboration. Bibliometric analysis has been used to extract data from Scopus database. patterns. A title search strategy using particular keywords search was used extracting a total of 331 records. The data was exported to VOS viewer software, Biblioshiny and Excel in order to generate a thorough scientific analysis. This study fills the gap by addressing the issue of international collaboration in data and AI ethics research, and cultural diversity perspectives in the realm of international studies. The findings revealed that 633 authors from 40 different countries have contributed to documents on data and AI ethics. This shows that only a few countries contributed to global research trends in data and AI ethics, indicating a dearth of different perspectives. Computer science and philosophy professors in Western colleges affect data and AI ethics discussions in technology and society journals. Oxford and Cambridge universities offer key viewpoints on the subject, while merely three main clusters of cross-country collaboration took place. This study highlighted the practical implication where emphasis is needed to increase international collaboration in data and AI ethics research to create a more inclusive and equitable global framework. The study serves as the foundation for increased collaboration, which may dispel negative stereotypes, develop social cohesion, promote tolerance, and foster improved decision-making and problem-solving.